(3Gdedd hGdfMds - (3eMeO Hf YHO GdcQje Hf CMeO GdTgQSJGfj,J (B548 (3g` s
(3ChdgG (B:s
(3GdMeO ddg MeO GdTGcQjf HLejY eMGeOg cdgG MeOkG cKjQkG deG habfi Gddg JYGdi GdeWGdYI ebGdGJ Cgd GdYde ef CQHGH GdOjGfGJ hGdedd hGdCghGA hGdfMd CQOJ Cf CLeY ai Pdc eNJUQkG jMhi eG JOjf Hg GdeJOjfhf s
(3BNQgG (B:s
(3gPG eG hLOJg ef ebGdGJ Cgd GdYGde , hfbdJg Ydi eG hLOJg , hGdMeO ddg hMOg s
(3jdGMX GNJdGa gPg GdfSNI Yf GdfSNI Qbe (B1601/ (3ESchQjGd adaXgG eNJUQkG YfgGs
(3Ydi GdfSNI JedcGf CMOgeG (B811 (3g`s
(3hGdKGfi (B961(3g`s
(3hgj ef cJH RjOGf Hf CMeO CejQ GdeDefjf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1820s
Keywords: (3GdJhMjO hGdedd hGdfMds